Multiferroics Fundamentals and Applications - Cano, Andrés; Meier, Dennis; Trassin, Morgan, ontributor; Bibes, Manuel; Bibes, Manuel; Bousquet, Eric; Bousquet, Eric; Bristowe, Nicholas C.; Bristowe, Nicholas C.; Campanini, Marco; Campanini, Marco; Davydova, Margarita D.; et al. (De Gruyter, 2021)
Multiferroics, materials with a coexistence of magnetic and ferroelectric order, provide an efficient route for the control of magnetism by electric fields. The authors cover multiferroic thin-film heterostructures, device architectures and domain/interface effects. They critically discuss achievements as well as limitations and assess opportunities for future applications.